Disruptive behaviour at workplace and dismissal - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Eishan Jan, Mohammad Naqib (LexisNexis, 2016)
This article focuses on the circumstances in which an employee's disruptive behaviour at the workplace would enables the employer to terminate the employment relationship with reference to Industrial Court's award.